2012
DOI: 10.1007/s13201-012-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

PEI modified Leucaena leucocephala seed powder, a potential biosorbent for the decontamination of arsenic species from water bodies: bioremediation

Abstract: Environmental contamination due to anthropogenic and natural sources is increasing day by day because of increase in population, industrialization and urbanization. Arsenic species released into the environment tend to persist indefinitely, circulating and eventually accumulating throughout the food chain, thus becoming a serious threat to the environment. The present study explores the effectiveness of Leucaena leucocephala seed powder (agricultural waste) in removing arsenic ions from aqueous solution. Batch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The reusability of biomaterial, the ability to detect very less concentrations of toxic metals in water, the high removal efficiency, no production of secondary compounds, low operating costs, and short operation times are some advantages of biosorption over other methods . Various biomaterials including plant biomass, agricultural waste, bacteria, fungi, and algae have been used to confiscate As from aqueous solutions . Other conventional methods described above have several technical and economical limitations due to which the biosorption process is gaining attention.…”
Section: As Removal Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reusability of biomaterial, the ability to detect very less concentrations of toxic metals in water, the high removal efficiency, no production of secondary compounds, low operating costs, and short operation times are some advantages of biosorption over other methods . Various biomaterials including plant biomass, agricultural waste, bacteria, fungi, and algae have been used to confiscate As from aqueous solutions . Other conventional methods described above have several technical and economical limitations due to which the biosorption process is gaining attention.…”
Section: As Removal Methodsmentioning
confidence: 99%
“…Metal ion complex formation, chemical and physical adsorption, ion exchange, and precipitation are some mechanisms which are involved in adsorption . In some cases, chemical modification has also shown promising results in improving the efficiency of adsorbent. Figure represents the mechanisms involved in As removal by fruit and vegetable wastes.…”
Section: As Removal Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al 31 achieved sorption of 55% of [As(V)] at pH 7.0, using cerium oxide nanoparticles. Raj et al 32 used industrial corn waste to remove [As(V)] from aqueous solutions at pH 7.5. The authors found that by crosslinking Zea mays cob powder with PEI the adsorption efficiency increased by 12%.…”
Section: Biosorption Of [As(v)] and [As(iii)] With Protonated Alginate Capsulesmentioning
confidence: 99%
“…They reported that the percentage sorption of As (III) increases from 22.04 (NCC) to 80.22% (aminated NCC), while percentage sorption of As (V) increases from 23.26 (NCC) to 91.56% (aminated NCC). Raj et al executed the batch studies toward the characterization of As (III) and As (V) removal capability of Leucaena leucocephala seed powder (LLSP). They observed the maximum biosorption capacity for As (III) and As (V) with the value of 81.88 and 92.61%, respectively.…”
Section: Introductionmentioning
confidence: 99%